Prevalence of severe acute respiratory syndrome coronavirus 2 spike antibodies in some healthcare settings in Egypt - Engy Mohamed El-Ghitany; Azza Galal Farghaly; Shehata Farag; Mona H. Hashish; Fahmy Charl; Eman A. Omran (SpringerOpen, 2022)
Abstract Background Healthcare workers (HCWs) are at the front line in battling infection transmission, such as that in coronavirus disease 19 (COVID-19). Additionally, they may act as potential carriers passing the virus on to others. Anti-spike (anti-S) antibodies for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are formed either as a result of infection or vaccination with both indicating immunity against future COVID-19 infection. Aim This study aimed to identify the prevalence of COVID-19 seropositivity among HCWs. Methods This cross-sectional study included 559 HCWs from 39 hospitals with variable degrees of COVID-19 exposure risk (depending on the occupation, department, and hospital type). Demographic data were recorded as well as history of COVID-19 infection and vaccination. Serum samples were collected and tested for SARS-CoV-2 spike antibodies. Results Anti-S positivity was found in 59.0% of the participating 559 HCWs, indicating a high level of seroprotection. Of the 559 HCWs, 34.1% had reported previous infection with COVID-19. Following infection, only 46 (24.0%) of those affected received vaccination. Anti-S seropositivity was found in 39.1% of participants who were unvaccinated and had no history of infection. Physicians had the highest median anti-S titers (58.0 relative units (RU)/mL), whereas pharmacists and office staff had the lowest (25.7 and 38.2 RU/mL, respectively). Conclusions Overall, 59.0% of the 559 HCWs were anti-S positive, indicating a relatively high seroprotective status. Among those who were unvaccinated and had no history of infection, 39.1% were seropositive for anti-S, denoting a high rate of silent/asymptomatic infections. Screening of HCWs for SARS-CoV-2 anti-S is recommended, along with the vaccination of seronegative individuals.